Stress induces behavioral sensitization, increases nicotine-seeking behavior and leads to a decrease of CREB in the nucleus accumbens - Leao, Rodrigo Molini [UNESP]; Cruz, Fabio Cardoso [UNESP]; Marin, Marcelo Tadeu [UNESP]; Planeta, Cleopatra da Silva [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Experimental evidence shows that exposure to stress engenders behavioral sensitization and increases drug-seeking and leads to intense drug taking. However the molecular mechanisms involved in these processes is not well known yet. The present experiments examined the effects of exposure to variable stress on nicotine-induced locomotor activation, cAMP-response element-binding protein (CREB) and extracellular signal-regulated kinase (ERK) activity and nicotine intravenous self-administration in rats. Male Wistar rats were exposed to variable stress that consisted of the exposure to different stressors twice a day in random order for 10 days. During this period the control group was left undisturbed except for cage cleaning. Ten days after the last stress episode, rats were challenged with either saline or nicotine (0.4 mg/kg s.c.) and the locomotor activity was recorded for 20 min. Immediately after behavioral recordings rats were sacrificed and their brains were removed to posterior western blotting analysis of CREB, phosphoCREB, ERR and phosphoERK in the nucleus accumbens. An independent set of control and stressed animals were subjected to an intravenous nicotine self-administration protocol. The break point during a progressive ratio schedule and nicotine intake patterns during a 24-hour binge was analyzed. Repeated variable stress caused a sensitized motor response to a single challenge of nicotine and decreased CREB in the nucleus accumbens. Furthermore, in the self-administration experiments previous stress exposure caused an increase in the break point and nicotine intake. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Stress; Nicotine; Self-administration; CREB; ERK